A corpus-based quantitative study on the interpersonal functions of hedges in Chinese and German academic discourse. Issue 9 (September 2022) - Yu, Quan; Wen, Renbai
Abstract: Hedge is one of the most essential ways of accomplishing interpersonal function. With its help, the speakers are able to say as much information as they could in the fewest possible words and better promote the interpersonal interaction while communicating, such as expressing politeness, providing more opportunities for further discussion, avoiding subjectivity, and boosting credibility. Therefore, hedge has become a commonly used interpersonal strategy for researchers. In this study, the corpus consists of 170 Chinese and 170 German academic articles from renowned linguistic empirical studies that were published between 2010 and 2019. Based on the theoretical research of prior studies, the interpersonal function of hedges and the similarities/differences of its pragmatic realization between Chinese and German academic written discourses are investigated from a quantitative perspective. It is concluded that the Chinese researchers are more cautious in using strong-modality-expressing-hedges. They communicate with readers indirectly and implicitly, focus on avoiding their own responsibilities, demonstrate a conservative and cautious attitude, and provide more room for further discussion, while the German researchers are considered more active in using those types of hedging strategies, which make them more direct while interacting with readers, concentrating on emphasizing the correctness of their own academic views and highlighting their positive attitude towards their own opinions. Abstract : Interpersonal function; Academic discourse; Hedge; Comparative study.